STRUKTUR KOMUNITAS MIKROARTROPODA TANAH DI LAHAN PENAMBANGAN GALIAN C ROWOSARI, KECAMATAN TEMBALANG, SEMARANG - Wiatri Larasati; Rully Rahadian; mochamad Hadi (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Rowosari miningsite isthe ‘C’ type of excavation area in Semarang. Mining activities may affect environmental disturbance, including on soil fauna. This research aims to determine the community structure of soil microarthropods in Rowosari mining area. The research was conducted in August-September 2015. Soil samples were taken on diagonal plot of 5x5 m2 with a five-point sampling on two stations, namely Post Mining Area (PoMA) and Pre Mining Area (PeMA). The analysis used in the research are relative abundance index, Shannon-Weiner diversity index, evenness index, and Sorensen similarity index. The results shows that there are 360-660 individuals/m2 from 10 ordo and 24 taxa found in Rowosari Excavation Site. The highest relative abundance index is Carabidae (22,22) in PoMA station and Prostigmata (21,21) in PeMA station. The diversity both station belongs to medium category (2,43-2,45). The highest evenness index is 0,95. The similarity taxa of soil microarthropods in two stations are categorized as medium. Community structure of soil microathropods in Post Mining Area and Pre Mining Areawere no significant differences. Keywords: Community structure, Soil microarthropods, MiningexcavationC.